Homologizing Accident: Notes on Warhol’s Car Crashes - Sarkar, Abhishek (EAST WEST JOURNAL OF HUMANITIES, 2013)
This paper focuses on some paintings by Andy Warhol depicting car crashes to demonstrate how he uses them not only to underscore the commodity fetishism of contemporary capitalism but also subversively to undermine such traits in contemporary American culture. It also explores the connection between the ambivalence reﬂected in the paintings and Warhol’s sexuality. In the process, it connects the paintings to the category Susan Sontag has famously categorized as “Camp” and Warhol’s own facetiousness and love of surfaces and mixed modes as well as gimmick and parody.